Impact of Heat Stress on Meat, Egg Quality, Immunity and Fertility in Poultry and Nutritional Factors That Overcome These Effects: A Review - Fouad, A.M. (International Journal of Poultry Science, 2016)
Modern strains of poultry have been produced to meet the demands of consumers in terms of quantity and they are affected by problems associated with immunity (sensitivity to infection with different diseases), stressors (high sensitivity to different stressors) and product quality (meat and egg quality). In particular, heat stress (HS) negatively affects the productive performance, meat yield, egg yield, meat quality (visual appearance and chemical characteristics), egg quality (internal and external), reproductive performance, intestinal functions and immune response. In addition, there is increased awareness among consumers of the quality of food and the industry must aim to satisfy the higher requirements of consumers. Thus, there is increased pressure on poultry producers to improve their production quantity and quality. As a consequence, it is important to know how HS affects the meat quality, egg quality, immune organs, intestinal functions and reproductive organs in order to protect against any negative effects. In addition, it is essential to determine the roles of nutritional factors and the possibility of using them to overcome the negative effects of HS. This review summarizes current research in these areas.